Physical balance of 12-13 year old adolescents in Latvia: problems and solutions - Ušča, Svetlana; Žogla, Irēna; Rutka, Lūcija (Social Welfare: Interdisciplinary Approach, 2016)
The paper is prepared within the framework of the National science programme “Innovative solutions for social telerahabilitation in the schools of Latvia in the context of inclusive education (INOSOCTEREHI)”. The paper focuses on the adolescents’ balance disorders. Equipment for balance testing BIOSWAY was used in the case study. It showed that almost every fourth adolescent of the age 12-13 years has the total postural stability index below the norm. Only 9.4% of adolescents have normal overall balance control results. It is necessary to find ways how to reduce the identified problem within the context of inclusive education.
Keywords: physical balance; 12-13 year old adolescents